Rethinking external environmental analysis for sustainable development: the case of a beverage manufacturing industry in a Southern African Country - Ruwanika, Eliot Quinz Farai; Massyn, Liezel (MDPI, 2024)
The advent of the United Nations Sustainable Development Goals (SDGs) Agenda 2030 ushered in a new way of thinking about the forces that drive change in the business environment. Literature suggests that sustainable development is a megaforce driving change globally and envelops the traditional political, economic, social, technological, and ecological (PESTE) forces approach. This article reframes the external environmental analysis to integrate SDGs into the business strategy of a beverage manufacturing industry. A qualitative design using snowball sampling resulted in semi-structured, face-to-face interviews that were audio recorded. Interviews were held with eight executives, one former executive, and three non-executive staff from four companies of a southern African country’s beverage manufacturing industry. The data exposed some ignorance on sustainable development. Many executives understood the importance of sustainable development without consensus on its exact nature and implementation in the organisational context. Thematic data analysis confirmed the relevance of sustainable development and the need to incorporate it in external environmental analysis. Categorising SDGs into a 5-P framework (people, prosperity, planet, peace, partnerships) and integrating it with the PESTE framework, the study provides a new approach/tool for external environmental analysis. This approach facilitates identification of SDGs that are relevant to business during strategic planning.
Keywords: Business strategy; external environmental analysis; PESTE; sustainable development; Sustainable Development Goals (SDGs)